Analysis of the School Environment on the Formation of Religious and Moral Values of 5-6 Year Old Children - Apriani , Lili (UNIB Press, 2025)
Early character building of religious and moral values is an important component of their development. This condition is characterized by the fact that many children's behavior is not in line with religious and moral teachings, requiring special attention from parents and schools. The purpose of this study was to examine the school environment's influence on the formation of moral and religious principles in children aged 5 to 6 years in Ogan Ilir District, South Sumatra. This survey research employed purposive sampling, involving 47 teachers from 6 kindergartens selected based on their location and characteristics in relation to the acquisition of religious and moral learning. Questionnaires were used to collect data, and descriptive statistics were used to examine four primary indicators: religious rituals, modesty norms, moral norms, and educator strategies. The results showed that moral norms were the primary focus in character building, followed by modesty norms and religious rituals. Children's understanding of religious holidays and ability to accept criticism still need to be improved, although the learning strategies implemented are effective. This study suggests implementing a more interactive and collaborative learning approach between teachers and parents to support children's character development.